ANALISIS KELENGKAPAN PENGISIAN LEMBAR CEKLIS KESELAMAAN PASIEN DI RUMAH SAKIT ICHSAN MEDICAL CENTRE BINTARO TAHUN 2017 - Beti Winda Yuliana; Vebry Haryati Lubis (STIKes IMC Bintaro, 2018)
In the health sector, the interaction between healthcare providers and recipients of health services is highly sustainable. So as to improve the quality of health services to be provided and to update a person's medical history, any health care content should be recorded.The problem that often arise in filling the medical record is the incomplete data filling, then the problem formulation in this research is how completeness of filling patient safety check list at IMC Hospital Bintaro.This research was conducted in RS. IMC Bintaro within the scope of Health Services Management. This research uses quantitative research method. The research design used is Descriptive.The results showed that the percentage of completeness of the patient safety check list at IMC Bintaro Hospital for May-October 2016 period (N = 150) resulted in 78% = 117 incomplete files and 22% = 33 complete files meaning no charging check patient patient safety operation .